Respuesta :
Answer:
- a) h(x) = 4log₃(x) + 2
- b) x = 9
Step-by-step explanation:
Given:
- f(x) = log₃(x) + 3
- g(x) = log₃(x³) – 1
Part A
Find h(x) = f(x) + g(x)
- h(x) =
- log₃(x) + 3 + log3(x³) – 1 =
- log₃(x) + 3log₃(x) + 2 =
- 4log₃(x) + 2
Part B
Assumed f(x) and g(x) system is to be solved.
Substitute log₃(x) = y, then:
- f(x) = y + 3
- g(x) = 3y - 1
Set them equal and solve for y:
- y + 3 = 3y - 1
- 3y - y = 3 + 1
- 2y = 4
- y = 2
Substitute back:
- log₃(x) = 2 ⇒ x = 3² ⇒ x = 9
Answer:
Part A: log3(x^4)+2
Part b: x=9
Step-by-step explanation:
ik you probably dont need the answer answer since u posted this a while ago but just in case someone else is searching for the answer too:) have a great day!:)